Efeitos das características da estrutura e composição do conselho de administração na qualidade da informação contábil no Brasil - Holtz, Luciana (2013)
This research was developed with the objective of investigating the effects of the characteristics of structure and composition of the board of directors on the quality of accounting information of the companies listed on the BM&FBovespa. Specifically, the characteristics of the board studied were the size and the independence of the board, and the separation of the roles of the president of the board and the chief executive of the business. The proxies for quality of accounting information were the value relevance of the accounting information and the informativeness of earnings. The sample includes non-financial firms listed on the BM&FBovespa with an annual liquidity higher than 0,001, during the period of 2008 to 2011. The data was collected from the Economática® data base and directly from annual reports and reference forms of firms available on the CVM or BM&FBovespa site. To reach the proposed objective the methodology of research consists in a quantitative approach based on Vafeas (2000), Firth, Fung and Rui (2006) and Habib and Azim (2008). The analysis of the data was based on the technique of multiple regression for the estimation of models of value relevance of accounting information and informativeness of earnings. The results indicate that in the Brazilian market, for firms that negotiate stock on the BM&FBovespa, the characteristics of independence of the board of directors and separation of the roles of president of the board of directors and of chief executive have a positive influence on the quality of the accounting information being reported, specifically on the relevance of the net equity. The informativeness of earnings is positively affected by the independence of the board of directors and negatively by the bigger boards (above nine members). The results in general corroborate with international studies such as Vafeas (2000), Firth, Fung and Rui (2006), Ahmed, Hossain and Adams (2006) and Dimitropoulos and Asteriou (2010), specially relating to the independence of the board of directors. Is possible to check that stronger governance structures exercise effects that improve the quality of accounting information reported.